Reaksi Investor Sebelum dan Sesudah Deklarasi Vladimir Putin Tentang Operasi Militer Khusus di Ukraina - Wicaksono, Crescentiano Agung (E-Jurnal Akuntansi, 2023)
The war that occurred between Russia and Ukraine had an impact on the world, especially related to security, defense and economic stability. This study aims to see the reaction of investors to Vladimir Putin's declaration regarding a special military operation in Ukraine on 24 February 2022. The research was conducted with 17 samples of plantation sector companies listed on the Indonesian Stock Exchange and using 31 days of observation. The research hypothesis was tested by conducting different tests on stock price and gold variables, as well as stock transaction volume using the Wilcoxon Signed Ranks Test. The results showed that there were differences in stock and gold prices before and after Vladimir Putin's declaration on special military operations in Ukraine, while there were no significant differences in the volume of stock transactions. This happens because investors want to secure their assets in stocks by diverting them to safe heaven instruments, one of which is gold. Keywords: Investor Reaction; Vladimir Putin; Gold Price; Stock Price